Mutation-Prone Positions Within the Estrogen Receptor - Viroj Wiwanitkit (Elsevier, 2009)
Objective: Estrogen is an important female hormone. The estrogen receptor (ER) plays a critical role in the development of breast cancer. Mutations within the ER can have clinically significant consequences. Materials and Methods: Identification of sites vulnerable to mutation is a new trend aimed at extending our knowledge of diseases at the genomic and proteomic levels. In this study, bioinformatics analysis was performed to determine the positions corresponding to specific peptide motifs in the amino acid sequence of the ER. A new computational tool called GlobPlot was used to identify the weak linkage positions within the ER. Results: The results allowed the identification of mutation-resistant positions. Conclusion: This study showed that the weak linkages within the ER could be identified, and these could provide the basis for further studies aimed at predicting possible new ER mutations.